Straightforward method for preparing a user-customizable DNA marker by improved overlap extension polymerase chain reaction - ZHANG Yuanyuan; YAN Yan; JIN Yulan; DONG Weiren; ZHOU Jiyong (浙江大学学报. 农业与生命科学版, 2019)
DNA marker is a set of standards that are used to indicate the approximate molecular-mass size of certain DNA fragment which separated by agarose gel electrophoresis. In the present study, a straightforward method for preparing a user-customizable DNA marker by an improved overlap extension polymerase chain reaction (PCR) was established. The DNA fragment, containing the identical sequence in its 5´ and 3´ ends, was amplified by a conventional PCR. In the following denaturation and annealing process performed by the overlap extension PCR, two single-stranded DNA in the 3´ end of which had complementary base sequences could form double-stranded DNA. In the extension process, these single-stranded DNA was utilized as both template and primer. The number of small fragments of DNA decreased and the number of large fragments of DNA increased gradually with the increased number of PCR cycles. The products of different cycles of overlap extension PCR were taken for agarose gel electrophoresis. The optimal PCR cycle or optimal combination of different PCR cycles was chosen according to the results of electrophoresis. Then 100 bp DNA ladder marker was obtained by the overlap extension PCR under the chosen condition. There was no need for purification of PCR products as the amplified fragments could be directly used in the agarose gel electrophoresis. The bands of prepared DNA marker were clear and accurate, and could be used for molecular studies. In sum, this method for DNA marker production is simple, time saving, cost effective, byproduct free and user-customizable in comparison with current ones widely used in most laboratories.